2017
DOI: 10.17645/si.v5i2.870
|View full text |Cite
|
Sign up to set email alerts
|

Peer- and Coach-Created Motivational Climates in Youth Sport: Implications for Positive Youth Development of Disadvantaged Girls

Abstract: The relationship between coach- and peer-created motivational climates and Positive Youth Development is largely unexplored. This is especially true for the latter and in particular with regard to disadvantaged girls. The present study was designed to examine the relationships between perceived coach- and peer-created climates and reported developmental gains among disadvantaged girls participating in sports programmes, and to determine whether these relationships were moderated by personal characteristics. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 42 publications
(81 reference statements)
1
11
0
1
Order By: Relevance
“…The results of this study supports research conducted by Schaillée, Theeboom and Van Cauwenberg (2017) who reported that the behaviours and actions of significant others (i.e. family, peers, coaches) have an important influence on the social development of young people.…”
Section: P3: "Dydych Chi Ddim Moen Ddefnyddio Geiriau O Tu Fewn Braweddegau Felsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study supports research conducted by Schaillée, Theeboom and Van Cauwenberg (2017) who reported that the behaviours and actions of significant others (i.e. family, peers, coaches) have an important influence on the social development of young people.…”
Section: P3: "Dydych Chi Ddim Moen Ddefnyddio Geiriau O Tu Fewn Braweddegau Felsupporting
confidence: 89%
“…and Schaillée, Theeboom and Van Cauwenberg (2017) also reported that a coach's actions and behaviours influence the social and personal development of a young person.…”
mentioning
confidence: 99%
“…Even more so, a negative or unbalanced sports climate could harm individual players and potentially push youths further down the spiral of vulnerability [ 60 , 61 ]. To fully understand the relationship between sports participation and youth development, assessing the quality of the sports climate, and thus the quality of the developmental experiences for youths [ 62 ], is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Youth sport environments characterized by a focus on performance and winning are often referred to in the literature as 'ego-involving' and have been linked with negative psychosocial and behavioural consequences (e.g., Duda & Balaguer, 2007;Newton et al, 2000;O'Rourke et al, 2013;Smith et al, 2008). Other studies in youth sport and physical education, however, have reported findings conflicting with the hypothesized link (e.g., Goudas & Biddle, 1994;Gould, Flett, & Lauer, 2012;Kipp & Weiss, 2015;Shaillée, Theeboom, & Van Cawenberg, 2017). At the same time, there is emergent evidence that complex environmental patterns, such as the one identified in this study, are associated with indicators of adaptive patterns of youth development in the family context (Gute, Gute, Nakamura, & Csikszentmihalyi, 2008), physical education (Goudas & Biddle, 1994) and youth sport (Authors, 2017;Horn, Byrd, Martin & Young, 2015).…”
Section: Discussionmentioning
confidence: 99%